2019
DOI: 10.1007/s12243-018-0695-7
|View full text |Cite
|
Sign up to set email alerts
|

On the rewards of self-adaptive IoT honeypots

Abstract: In an era of fully digitally interconnected people and machines, IoT devices become a real target for attackers. Recent incidents such as the well-known Mirai botnet, have shown that the risks incurred are huge and therefore a risk assessment is mandatory. In this paper we present a novel approach on collecting relevant data about IoT attacks. We detail a SSH/Telnet honeypot system that leverages reinforcement learning algorithms in order to interact with the attackers, and we present the results obtained in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Discussions of specific parts of RL solution design problems occur in smaller number of cases, but these kinds of publication demonstrate the fact that constructing an appropriate RL application is not always trivial. We can highlight state space design [12,25,33,107,144,179,193,208,217,220,222,224,227,266,267] and action space design [109,220,246,268], reward construction [14,76,110,199,220,226,246,[269][270][271][272][273], and exploration strategy planning [86,274] which can be determinants from the whole application point of view. [11,13,17,20,21,24,38,43,61,62,66,69,82,89,…”
Section: Complexitymentioning
confidence: 99%
“…Discussions of specific parts of RL solution design problems occur in smaller number of cases, but these kinds of publication demonstrate the fact that constructing an appropriate RL application is not always trivial. We can highlight state space design [12,25,33,107,144,179,193,208,217,220,222,224,227,266,267] and action space design [109,220,246,268], reward construction [14,76,110,199,220,226,246,[269][270][271][272][273], and exploration strategy planning [86,274] which can be determinants from the whole application point of view. [11,13,17,20,21,24,38,43,61,62,66,69,82,89,…”
Section: Complexitymentioning
confidence: 99%
“…Honeypots and related technologies, e.g., honeyfiles, honeynet, honeybot, etc., have been widely used to mitigate stealthy and deceptive attacks. In particular, RL has been widely used to develop self-adaptive honeypots in normal conditions [76,77,78] and resource-constrained environment [79]. As attackers become more sophisticated, they manage to fingerprint and evade honeypots [80].…”
Section: Information-related Vulnerabilitymentioning
confidence: 99%
“…With this data, he applied game-theory and Machine Learning (ML) techniques to develop a self-adaptive SSH honeypot called Adaptive Honeypot Alternative (AHA) [63]. While Wagener does not implement his honeypot in an IoT environment, his honeypot serves as the basis for Pauna's works [49], [56], [57], [64]. Wagener reported that attackers carried out three times more interactions when they were responding to the customized tools of an adaptive honeypot, which shows the important role that adaptive honeypots can play in honeypot research.…”
Section: A General Application Honeypotsmentioning
confidence: 99%
“…Pauna's honeypot resides on the Argos emulator as a guest OS, and utilizes Argos to detect rootkit malware. This research was followed by [56], [57], [64].…”
Section: A General Application Honeypotsmentioning
confidence: 99%
See 1 more Smart Citation